The Association of Fibroblast Growth Factor 23 with Arterial Stiffness and Atherosclerosis in Patients with Autosomal Dominant Polycystic Kidney Disease - Melahat Coban; Ayca Inci; Ustun Yılmaz; Emre Asilturk (Karger Publishers, 2018)
Background/Aims: In patients with autosomal dominant polycystic kidney disease (ADPKD), cardiovascular events are the most frequent cause of mortality and morbidity. The aim of our study is to investigate the association between serum fibroblast growth factor-23 (FGF-23) and arterial stiffness (AS) as determined with brachial-ankle pulse wave velocity (baPWV) and atherosclerosis development as determined with carotid artery intima-media thickness (CA- IMT). Methods: This cross-sectional study was conducted with totally 86 ADPKD patients, 50 (58.1%) female and 36 (41.9%) male, with a mean age of 49.5 ± 13.9 years. Patients were compared with healthy control group with similar distribution of age and gender. AS was assessed with baPWW, and atherosclerosis development was assessed with CA-IMT. CA-IMT > 9 mm was considered as increased atherosclerosis. Serum FGF-23 and soluble klotho (s-KL) levels were measured with enzyme-linked immunosorbent assay. Due to skewed distribution of variables, statistical calculations of FGF-23 and s-KL were performed with log10. Results: According to the CKD stages, 46 (53.5%) patients had stage 1-2, 32 (37.2%) had stage 3-4, and 8 (9.3%) had predialysis stage 5 disease. Mean log10FGF-23 was 2.43 ± 0.41 pg/mL, and mean log10s-KL was 1.28 ± 0.09 ng/mL. Mean baPWV was 7.48 ± 1.68 m/sec, and mean CA-IMT was 0.63 ± 0.14 mm. Among patients at various stages of CKD, systolic blood pressure (SBP) (p = 0.003), diastolic blood pressure (DBP) (p = 0.002), creatinine, 1.25hydroxy(OH)2VitaminD3, log10FGF-23, baPWV, CA-IMT were higher (p < 0.001)andlog10s-KL were lower (p < 0.001) in comparison to healthy individuals. FGF-23 was positively correlated with creatinine, 1.25(OH)2VitD3 (p < 0.001), baPWV (p = 0.002) and CA-IMT (p = 0.005), and negatively correlated with eGFR (p < 0.001). Conclusion: In patients with ADPKD, as the disease stage advanced, serum FGF-23 levels increased while s-KL decreased. In ADPKD patients, AS and atherosclerosis development increased as compared to healthy subjects, and as CKD advanced. In ADPKD patients, the effect of serum FGF-23 on the development of AS and atherosclerosis in peripheral vessels is independent of s-KL.